Simultaneous Ipsilateral Quadriceps and Triceps Tendon Rupture in a Patient with End-Stage Renal Failure. (5th August 2018) - Moerenhout, Kevin; Gkagkalis, Georgios; Benoit, Benoit; Laflamme, Georges Yves
Abstract : Introduction . Quadriceps tendon ruptures (QTR) frequently occur in patients with end-stage renal failure, while triceps brachii tendon ruptures (TTR) are less common. This is the first properly documented report of a simultaneous ipsilateral traumatic rupture of both of these tendons. Case Report . A 50-year-old patient, on hemodialysis for end-stage renal failure, fell on his right side. He presented with sudden right knee and elbow pain, with functional impairment of both joints. X-rays showed avulsion-like osseous lesions on the olecranon and patella with a low-riding patella. Ultrasound confirmed complete quadriceps and triceps avulsion ruptures. Both lesions were treated surgically. Fixation was performed with anchors using the Krackow suture technique for both tendons. Postoperative clinical and radiological results were satisfactory, and follow-up was uneventful. The patient regained his preinjury functional level with a complete range of motion of both his knee and elbow. Discussion . Isolated QTR and TTR are frequent lesions in chronic renal failure patients treated with hemodialysis. Simultaneous ipsilateral rupture of both tendons however is extremely rare and should therefore not be overlooked. Surgical treatment is recommended for complete ruptures.